Pelatihan Penyelesaian Soal Tpa Bagi Alumni Dan Calon Alumni Program Studi Pendidikan Matematika Universitas Katolik Weetebula - Kaleka, Yohanis Umbu; Making, Samuel Rex Mulyadi (CV. Global Cendekia Inti, 2023)
TPA is a test that is often used in job searches by both government and private companies. The Mathematics Education Study Program at Weetebula Catholic University needs to prepare and equip its alumnae and prospective alumnae to be able to compete in the world of work. The TPA question categories used in this training are the verbal category, the number sequence pattern category, the Venn diagram category, the proposition logic category, the analytical logic category and the mathematical reasoning category. This training was carried out using lecture and discussion methods. Before carrying out the activity, a pretest is carried out first. Meanwhile, at the end of the activity, a posttest was carried out. The average value of the pretest results for the verbal category is 40.74, the average value for the Number Patterns category is 51.11, the average value for the Venn diagram category is 48.89, the average value for the prepositional logic category is 33 .33, the average value for the analytical logic category is 35.55 and the average value for the mathematical reasoning category is 53.33. Meanwhile, the average value of the posttest results for the verbal category is 66.67, the average value for the Number Patterns category is 66.67, the average value for the Venn diagram category is 73.33, the average value for the prepositional logic category is 73.33, the average score for the analytical logic category is 70 and the average score for the mathematical reasoning category is 76.67. This shows that there has been an increase in understanding among participants in training activities